Analysis Of The Influence Of Financial, Environmental Performance And Corporate Governance On Performance Of Corporate Social Responsibility Of Energy And Mineral Companies Listed In Indonesian Stock Exchange - Festus Evly R.I. Liow; Imam Hanafi; Loso Judijanto; Tanti Widia Nurdiani; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to determine how company governance, financial performance, and environmental performance affect the disclosure of corporate social responsibility. With secondary data from all energy businesses that have released annual reports, this study employs quantitative methodologies. All companies in the energy sector listed on the Indonesian Stock Exchange comprise the population considered in this study. Purposive sampling was used as the technique for selecting the sample. The partial least squares (PLS) approach is the data analysis technique employed in this study. Microsoft Excel was utilized by researchers to do descriptive statistical computations. The evaluation of the PLS model, which consists of two models, the outer model and the inner model, comes next once descriptive statistics have been completed. Disclosure of corporate social responsibility is positively and significantly impacted by corporate governance using KP, DKI, and KA indices. This demonstrates that a company's corporate social responsibility disclosure is more widely disclosed the better its governance. Disclosure of corporate social responsibility is positively and significantly impacted by environmental performance as measured by the PROPER indicator. This demonstrates that greater corporate social responsibility disclosure corresponds with improved environmental performance. The relationship between financial performance as measured by NPM, ROA, and ROE and corporate social responsibility disclosure is nonexistent. This demonstrates that a company's level of corporate social responsibility disclosure is not always influenced by its financial performance.